Study of Rheological Behavior of Bottom Ash With Additives - Sharma, Sandeep (My University, 2012)
Slurry pipelines are used to transport solid materials using water or any other liquid as a carrier fluid for short or long distance haulage of bulk materials. These pipelines are used in may industrial applications involving transportation of variety of materials like mineral ores to processing plants, coal to thermal power plants, disposal of waste materials like fly ash, tailings materials etc. Slurry pipeline has been accepted as a safe, reliable and attractive mode of solid transportation by various industries, due to its low maintenance, round the year availability and being eco-friendly. One of the most important input data needed for the design of the slurry transportation system is the rheological behavior of the slurry at various concentrations and flow conditions. The rheological properties of slurries must be determined as accurately as possible under conditions that closely resemble actual site conditions rheological behaviors.. In the present study reports the effect of additive rheological characteristic of bottom ash slurry at high concentration for bottom ash with or without additive . Sodium bi carbonate has been used as additive. Rheological study are also carried out with bottom ash and fly ash mixture slurry at different concentration A good agreement is observed between experimental data and model (prediction). The plots reveal that the viscosity of the suspension increases with increasing solid concentrated Rheological behavior with addition of fly ash and additive observe that viscosity value decreases. The study indicated that the viscosity is very much sensitive to the concentration of solids..
MED (CAD/CAM and Robotics)
Keywords: Bottom Ash; Rheology; Additives; Slurry Pipelines